Paradoxical Potentiation of Acid-Sensing Ion Channel 3 (ASIC3) by Amiloride via Multiple Mechanisms and Sites Within the Channel - Matasic, Daniel S.; Holland, Nicholas; Gautam, Mamta; Gibbons, David D.; Kusama, Nobuyoshi; Harding, Anne M. S.; Shah, Viral S.; Snyder, Peter M.; Benson, Christopher J. (Frontiers in Physiology, 2021)
Acid-Sensing Ion Channels (ASICs) are proton-gated sodium-selective cation channels that have emerged as metabolic and pain sensors in peripheral sensory neurons and contribute to neurotransmission in the CNS. These channels and their related degenerin/epithelial sodium channel (DEG/ENaC) family are often characterized by their sensitivity to amiloride inhibition. However, amiloride can also cause paradoxical potentiation of ASIC currents under certain conditions. Here we characterized and investigated the determinants of paradoxical potentiation by amiloride on ASIC3 channels. While inhibiting currents induced by acidic pH, amiloride potentiated sustained currents at neutral pH activation. These effects were accompanied by alterations in gating properties including (1) an alkaline shift of pH-dependent activation, (2) inhibition of pH-dependent steady-state desensitization (SSD), (3) prolongation of desensitization kinetics, and (4) speeding of recovery from desensitization. Interestingly, extracellular Ca2+ was required for paradoxical potentiation and it diminishes the amiloride-induced inhibition of SSD. Site-directed mutagenesis within the extracellular non-proton ligand-sensing domain (E79A, E423A) demonstrated that these residues were critical in mediating the amiloride-induced inhibition of SSD. However, disruption of the purported amiloride binding site (G445C) within the channel pore blunted both the inhibition and potentiation of amiloride. Together, our results suggest that the myriad of modulatory and blocking effects of amiloride are the result of a complex competitive interaction between amiloride, Ca2+, and protons at probably more than one site in the channel.